Analisis Pengaruh Kurs Dollar, Inflasi, dan Produksi Terhadap Ekspor Ikan Hias Di Provinsi Bali - Khoironi, Fitria Eviana; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 3, Maret 2017 (pp. 286-471), 2017)
Bali Province has a wealth of diverse of natural marine, one of the sector that is being developed by the government is the production of ornamental fish with various species are spread across the Bali island. Trends of hobby to keep the ornamental fish become popular in many countries that affect increase sum of ornamental fish export. The aims of this research is determine the effect of US dollar exchange rate, inflation, and production simultaneously and partial reserve to export of ornamental fish in Bali Province on period 1991-2015. The data used is secondary data, using Multiple Linear Regression Analysis. The results showed that simultaneous variabels of dollar exchange rate, inflation and production influenced reserves have significantly influence ornamental fish export in Bali Province in 1991-2015. Partially can be concluded that : (1) the dollar exchange rate reserveshave positive effect and significant to ornamental fish export, (2) inflation did notreserves affect significantly to ornamental fish export, (3) production reservers have positive effect and significant to ornamental fish export. The ornamental fish production of fisherman is dependent on catches from the sea, fishermen are expected to start using transfer technology to cultivation of ornamental fish in order to increase the amount of ornamental fish production.
Keywords: Ornamental Fish Export, Dollar Exchange Rate, Inflation, and Production.